TOURISM DEVELOPMENT STRATEGY THROUGH TOURIST EXPERIENCE EVALUATION (A Study on Suroboyo Carnival Park) - Warid Ajeng Yulibag (Jurnal Ilmiah Mahasiswa FEB, 2016)
The background of this study is the decreasing level of tourist’s revisiting intention, which is a phenomenon in tourism development. The number of tourist or customer is important for tourism service business since the feeling of the tourists will make them revisit if they are satisfied, or not if they are disappointed. This study was categorized into explorative study. According to Malhotra (2004), the objective of explorative study is to discover reasons behind a phenomenon through its problem and chance. The data of this study were collected through interview and observation and analyzed using qualitative analytical method. The result of this study is processed through SWOT analysis, aimed at comparing and determining the strategy with the best chace.Key words : Tourist experience, satisfying, strength, weakness, opportunities, threats